Pengaruh Integrasi Model Pembelajaran Everyone Is the Teacher Here dan Two Stay Two Stray Terhadap Keterampilan Bernegosiasi (Studi Eksperimen pada Kelas X di SMA Negeri 6 Palu) - Nurul Iffah Agam Zuhdi; Fathiaty Murtadho; Reni Nur Eriyani (LPPM Institut Pendidikan Nusantara Global, 2026)
This study investigates the effect of integrating the Everyone Is the Teacher Here and Two Stay Two Stray cooperative learning models on senior high school students’ negotiation speaking skills. The research employed an experimental method using a one-group pretest–posttest design. The participants were 32 tenth-grade students at a public senior high school in Palu, Indonesia. Data were collected through oral negotiation performance tests assessed using a validated rubric covering negotiation stages, language use, content relevance, articulation, tone, and attitude. The results show a significant improvement in students’ negotiation skills after the implementation of the integrated learning models. The mean score increased from 74.38 in the pretest to 85.25 in the posttest. Statistical analysis using a paired sample t-test revealed a significant difference between pretest and posttest scores (Sig. = 0.001 < 0.05). Furthermore, the normalized gain analysis yielded an average N-Gain score of 0.36 (36%), indicating a moderate level of effectiveness. Qualitative observations also revealed improvements in students’ ability to present structured arguments, apply appropriate negotiation stages, use polite and persuasive language, and demonstrate clearer articulation and more confident speaking attitudes. In conclusion, the integration of Everyone Is the Teacher Here and Two Stay Two Stray is effective in enhancing students’ negotiation speaking skills and supports the development of communicative competence through collaborative and student-centered learning.